Biological corrosion behaviour and antibacterial properties of Ti-Cu alloy with different Ti2Cu morphologies for dental applications. (March 2022) - Xin, Cheng; Wang, Nan; Chen, Yongnan; He, Binbin; Zhao, Qinyang; Chen, Lei; Tang, Yufei; Luo, Binli; Zhao, Yongqing; Yang, Xiaokang
Graphical abstract: Highlights: The Ti2 Cu of corrosion activity is composed of a "micro-galvanic cell" with α-Ti. The lamellar Ti2 Cu increased the Cu ion release caused by more galvanic interface. The antibacterial rate of L-Ti2 Cu is 99.5 %, due to the rapid release of Cu ions. Abstract: The influence of morphology of the Ti2 Cu phase on biological corrosion and antibacterial properties of Ti-Cu alloy was investigated by micro-galvanic corrosion. Elongated "micro-galvanic cells" were formed between lamellar Ti2 Cu phase (L-Ti2 Cu) and α-Ti matrix due to the different Volta potentials. The corrosion rate ( V corr ) of L-Ti2 Cu was twice that of granular Ti2 Cu phase (G-Ti2 Cu) because lamellar Ti2 Cu phase had more galvanic interface. The release of Cu 2+ ions in L-Ti2 Cu was 55 % higher than G-Ti2 Cu, reaching 99.5 % of the antibacterial rate in L-Ti2 Cu and providing a great potential in clinical application for dental implants.